2004
DOI: 10.2307/3345856
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Children's Pitch-Matching Accuracy in Relation to Participation in Cantonese-Immersion Preschools

Abstract: Researchers in several recent studies have investigated the relationships between pitch-matching accuracy and the native language of children (Chen-Haftek, 1999; Rutkowski, Chen-Haftek, & Gluschanoff, 2002;Trollinger, 2003), as well as vocal use in singing by bilingual children (Mang, 1999). In these studies, the results suggested that significant relationships exist between how the child used the voice in speech and how the child matched pitch (e.g., Trollinger, 2003) or sang specific songs (e.g., Chen-Haftek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…With young children, there is a connection between singing in tune and vocal use with language (Mang, 2006;Trollinger, 2003Trollinger, , 2004. Children who speak both Chinese and English are at an advantage in singing in tune and using their voices healthfully.…”
Section: Shared Connections Between Singing Language and Tone Colormentioning
confidence: 99%
“…With young children, there is a connection between singing in tune and vocal use with language (Mang, 2006;Trollinger, 2003Trollinger, , 2004. Children who speak both Chinese and English are at an advantage in singing in tune and using their voices healthfully.…”
Section: Shared Connections Between Singing Language and Tone Colormentioning
confidence: 99%
“…While many music teachers try to do this, we finally have the scientific findings to back that strategy. In my research, I consistently found that children near age 5 or younger had difficulty singing middle C without engaging in any pressed phonation (Trollinger, 2003(Trollinger, , 2004.…”
Section: Children Have Accessible Pitches and Available Pitchesmentioning
confidence: 65%
“…I believe what happened is that this was more of a measurement of and subsequent accommodation of vocal adjustment misbehaviors, especially as lower voices among males and females became generally more popular in pop singing and children tried to imitate those kinds of vocal models. Music textbook series added songs that reflected that trend, by including songs that are pitched well below middle C. While these lower notes are more comfortable for mature voices, they aren't as comfortable or as easily attainable for young voices (Trollinger, 2003(Trollinger, , 2004.…”
Section: Children Have Accessible Pitches and Available Pitchesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually the task of creating a story was added. All of the singing skills have been investigated individually by other researchers, for example, vocal range (Rutkowski, 1990(Rutkowski, , 2002Welch, 1979), pitch or pattern matching (Apfelstadt, 1984;Demorest & Clements, 2007;Flowers & Dunne-Sousa, 1990;Sims, Moore, & Kuhn, 1982;Stadler Elmer, 1990;Trollinger, 2003Trollinger, , 2004Wolf, 2012;Yarbrough, Bowers, & Benson, 1992), production of a familiar song with and without words (Adachi & Carlsen, 1995;Adachi & Trehub, 1998;Davidson, 1985;Trehub, Zhou, Plantinga, & Adachi, 2011), learning an unfamiliar song (Rutkowski, 1990(Rutkowski, , 2002Stadler Elmer, 2000, 2001, and the creation of an original song (Adachi & Trehub, 1999Davidson, 1985;Stadler Elmer & Hammer, 2001). What is unique about the ATBSS is the examination of all of these together and with the aim of doing this systematically across the lifespan, across levels of musical training, and across cultures.…”
Section: Introductionmentioning
confidence: 99%